Образование нанолистов оксигидроксидов алюминия из электровзрывных нанопорошков - Сваровская Н. В. Наталья Валентиновна; Бакина О. В. Ольга Владимировна; Глазкова Е. А. Елена Алексеевна; Лернер М. И. Марат Израильевич; Псахье С. Г. Сергей Григорьевич (2010, 2010)
Заглавие с экрана